An integrated framework for optimizing large hydro–photovoltaic hybrid energy systems: Capacity planning and operations management. (15th July 2021) - Ming, Bo; Liu, Pan; Cheng, Lei
Abstract: Synchronous resolution of capacity planning and operations management sub-problems of large hybrid energy systems (HESs) may further enhance the synergy between different energy sources. However, these two sub-problems constitute a complex bi-level programming problem, which is difficult to effectively solve. In this study, we proposed an effective framework to synchronously determine the optimal photovoltaic (PV) size and long-term operating rules for large hydro–PV HESs. Firstly, a set of short-term operation models for each possible PV size were established to simulate joint operation processes of hydropower and PV power. Then, PV-energy loss functions were derived based on short-term simulation results and they were subsequently incorporated into long-term optimal operation models, aiming to maximize net energy production of the HES. Thirdly, long-term operating strategies were optimized by dynamic programing and sampled using a bootstrap method to generate inputs for a capacity planning model. Finally, the optimal PV size was determined by maximizing the net present value of the PV plant over its life-span, while operating rules were obtained using a regression analysis method. A case study was carried out using China's Longyangxia hydro–PV HES. The results showed that: (1) the integrated framework could synchronously yield optimal PV size and operating rules for the HES without heavy computational burden; (2) the capacity planning model could provide an optimal PV size of 880 MW with a confidence interval of [820, 930] MW; and (3) the derived operating rules outperformed the conventional reservoir operating rule curves in terms of power generation and water supply performances. Therefore, the proposed framework can be an effective tool for the planning and management of large hydro–PV HESs. Highlights: New framework developed to optimize operating rules and photovoltaic system size. Long- and short-term models used to simulate hybrid system operations. Sizing model plus bootstrap provided optimal photovoltaic size.